2016
DOI: 10.1002/2016jc011637
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying mesoscale eddies in the Lofoten Basin

Abstract: The Lofoten Basin is the most eddy rich region in the Norwegian Sea. In this paper, the characteristics of these eddies are investigated from a comprehensive database of nearly two decades of satellite altimeter data (1995–2013) together with Argo profiling floats and surface drifter data. An automated method identified 1695/1666 individual anticyclonic/cyclonic eddies in the Lofoten Basin from more than 10,000 altimeter‐based eddy observations. The eddies are found to be predominantly generated and residing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 78 publications
9
59
0
Order By: Relevance
“…Irminger Current Anticyclones (or Irminger Rings) play an important role in the advection of heat into the central Labrador Sea due to their anomalous warm cores, and are argued to account for between 25 and 100% of the heat needed to balance the surface heat loss during wintertime [ Lilly et al ., ; Katsman et al ., ; Hátún et al ., ; Rykova et al ., ; Fan et al ., ]. Similar to Lofoten Eddies (see an example at 10°E, Figure ) shed from the slope current [ Köhl , ; Raj et al ., ; Søiland et al ., ], Irminger Rings are triggered from the west Greenland boundary current over steep topography [ Lilly et al ., ; Katsman et al ., ; Hátún et al ., ; Rykova et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Irminger Current Anticyclones (or Irminger Rings) play an important role in the advection of heat into the central Labrador Sea due to their anomalous warm cores, and are argued to account for between 25 and 100% of the heat needed to balance the surface heat loss during wintertime [ Lilly et al ., ; Katsman et al ., ; Hátún et al ., ; Rykova et al ., ; Fan et al ., ]. Similar to Lofoten Eddies (see an example at 10°E, Figure ) shed from the slope current [ Köhl , ; Raj et al ., ; Søiland et al ., ], Irminger Rings are triggered from the west Greenland boundary current over steep topography [ Lilly et al ., ; Katsman et al ., ; Hátún et al ., ; Rykova et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…We call this anticyclonic eddy the Lofoten Basin Eddy (LBE). Since then, several studies addressed the mesoscale activity in the basin using observations of hydrography [ Ivanov and Korablev , ; Rossby et al ., ; Raj et al ., ], numerical models [ Köhl , ; Volkov et al ., ], satellite altimetry [ Raj et al ., ; Søiland et al ., ], and surface drifters and subsurface floats [ Rossby et al ., ; Voet et al ., ; Andersson et al ., ; Koszalka et al ., ; Søiland and Rossby , ]. Lagrangian studies described the pathways, eddy kinetic energy, lateral mixing rates in the basin, as well as position and radius of LBE.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Eddy detection in the Lofoten Basin using this method has also been validated using Argo floats and surface drifters (Raj et al 2016). Raj et al found that the altimeter-derived geostrophic speeds of eddies are roughly 25-30% lower than the geostrophic speeds of surface-drifters co-located inside eddies.…”
Section: Eddy Detection Methodsmentioning
confidence: 99%
“…However, the eddy activity of the Lofoten Basin in terms of its physical properties remained less explored. It is only recently that a study (Raj et al 2016) quantified the mesoscale eddies of the Lofoten Basin using a combination of gridded altimeter, Argo floats, and surface drifter data.…”
Section: Introductionmentioning
confidence: 99%